Microbes and sustainable production of biofuel crops: a nitrogen perspective. Issue 6 (November 2010) - Germaine, Kieran J; Chhabra, Sagar; Song, Bongkeun; Brazil, Dina; Dowling, David N
Green energy and biofuel policy is promoting the replacement of a significant percentage of fossil fuel resources with renewable bioenergy carriers to meet future energy requirements and reduce carbon emissions. However, the global rise in nitrogen pollution, due to increased food and biofuel crop production, has raised environmental concerns. Strategies for managing sustainable energy production while maximizing the benefits should be an important milestone for all biofuel-producing countries. In this article we review the recent literature concerning the use of chemical and biological fertilizers on biofuel crops and the role of the microbial nitrogen cycle in the nitrate and nitrous oxide emissions from various environments. The future potential of microbes for the sustainable production of biofuel-energy crops is discussed.